The Chain Mediating Effect of the Public's Online Health Information-Seeking Behavior on Doctor-Patient Interaction - Luo, Aijing; Yu, Zhen; Liu, Fei; Xie, Wenzhao (Frontiers in Public Health, 2022)
Objective: This paper aims to explore the influence mechanisms of online health information-seeking behavior (OHISB) on doctor-patient interactions (DPI) from a psychological perspective, using theory as a guide，which can effectively guide the mode of doctor-patient interaction after searching behavior in China. Methods: We conducted a convenient Web-based survey among members of the public who engage in searching behavior in China using a pretested structured questionnaire. Structural equation modeling was performed for path analysis and mediating effect testing. Results: The findings of the study show that (1) perceived disease severity (PDS)(95% CI: 0.003, 0.04, P <0.001), perceived action benefits (PAB) ( 95% CI: 0.059, 0.138, P <0.001), and e-health literacy (EHL) (95% CI: 0.061, 0.155, P <0.001) were positive predictors between OHISB and DPI. (2) The EHL → PDS (95% CI: 0.001, 0.013, P <0.05) and EHL → PAB (95% CI: 0.082, 0.166, P <0.001) paths are positive predictors between OHISB and DPI. Conclusions: EHL, PDS, and PAB act as a chain mediator between OHISB and DPI.